ä½¿ç”¨å›¾ç‰‡æ•™å¦æé«˜åœ£çˆ¶åˆä¸äºŒå¹´çº§Fçå¦ç”Ÿå¯¹è¯è¯çš„è®¤è¯»èƒ½åŠ› - Iasha, Yoshica; ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractVocabularies teaching is an important part that shape the mandarin language learning, because without it the students not able to express something in chinese language. The teaching of mandarin language covers of three parts ?meanings, pronunciation and word form?. The dificulties in learning mandarin that often happens is recognizing the vocabularies, especialy after the teachers explained it, the students understand the meanings, pronunciation and characters but at test session they can not correctly recognizing the vocabularies. In order to help students get deeper recognizing in chinese characters, the writer did a research. Writer did a test to a 2F students at smp Bruder in order to know their first condition, after that using images to enter characters teaching session in three times meeting. After teaching using this method, writer do a final test to the students. Writer able to know ability of students in recognizing and reading the vocabularies acording first and final test: In choosing chinese characters part of the images incresed 29,5%; choosing pinyin part of the images increased 19%; fill the blank part increased 14,5%. This research shows using images in teaching can help students to improve their ability in recognizing the vocabularies.Keyword : Vocabularies, Images Media, Recognize Vocabularies Teaching